THE ROLE OF PARATHYROID HORMONE-RELATED PROTEIN IN PATHOGENESIS OF DISORDERS OF BLADDER CONTRACTILE FUNCTION - V. I. Medvedev; A. N. Kurzanov (Кубанский научный медицинский вестник, 2018)
Aim. Based on the analysis of the scientific literature sources, the authors aimed to summarize and present the existing information about the role of parathyroid hormone-related protein (PTHrP) in pathogenesis of disorders of bladder contractile function.Materials and methods. Analysis of literature in databases Google Scholar, Scopus, Web of Scence, PabMed for the whole time period of studying the stated problem.Results. In the recent years, one can observe a growing interest to dysfunction of bladder with insuffi contractile activity of detrusor. The low level activity of bladder can be often observed, while its diagnostics and treatment remain problematic. The existing ideas about the role of parathyroid hormone-related protein (PTHrP) in regulation of bladder’s functional condition are based on the results of few and mostly experimental research studies. It is proved that PTHrP secretion is induced in bladder as a result of bladder stretching, and prevents spontaneous contraction of detrusor’s smooth muscles, which has PTH/PTHrPreceptors, and also reduces contraction amplitude of bladder. It was stated that increased PTHrP secretion in response to the stretching smooth muscles is a part of autocrine effect, relaxing the bladder during its fi The existing scientifi data show that PTHrP is a unique endogenous detrusor relaxant, which functions by means of PTH/PTHrP-receptors located in bladder. It is assumed that PTHrP can also have a paracrine effect on vessels that regulate the blood fl bladder fi or can change neural activity. Thus, PTHrP is a powerful endogenous relaxant of bladder contraction, while autocrine or paracrine mechanisms of this effect are physiologically relevant processes happening in bladder. It is assumed that disturbed binding PTHrP with its receptor can be part ofpathogenesis of bladder disorders. In our opinion, the infl of chronic high PTHrP level in blood fl on the detrusor muscle structures can be also considered as one of the reasons that cause functional insuffi of bladder. This assumption is based on comparison of the PTHrP-effects on the bladder functional condition, presented in the experiment, as well as in the few clinical studies. Direct infl targeting the interaction of PTHrP with its specifi PTH/PTHrP-receptor is considered as a potential therapeutic approach to treat pathological conditions related to disorder of bladder contractile function.Conclusion. The literature survey covers general ideas about functional insufficiency of bladder, as well as information about the role of PTHrP in its development. The studied problem is rather relevant and frequent in the population, and besides being seen as a urological pathology, it is associated with a considerable reduction of the quality of life for patients. More detailed clinical studies will let us specify the diagnostics criteria of this syndrome and develop the schemes for pathogenetic therapy.